Unfit for Work, Fit for Firearm or driving license - Is that Possible? - Lalić, Hrvoje (Open Access Maced J Med Sci, 2019)
BACKGROUND: Psychiatric disorders are not compatible with carrying firearms or with driving a car. Persons with such disorders are often not employed and are persistent in demanding invalidity pensions, but some of them also insist on holding on to the mentioned licenses. In such cases, where persons are already in possession of firearms and driving licences, it never occurs to them, that they should surrender their permits back. AIM Pointing to the importance of OM controlling firearm/car driving licenses. CASE REPORTS: This paper discusses the problem of three cases that should be widely recognised as it is potentially life-threatening to other people. The first is the case of a war veteran in retirement with PTSD that had his application for firearms licence rejected by the authorities. The second is the case of a labourer who suffers from a depressive disorder, temporarily incapable of work. The third is the case of a war veteran, a chronic alcoholic with toxic epilepsy, who is applying for invalidity retirement but wants to keep his driving license. CONCLUSION: Occupational medicine assess every single worker by applying advanced methods and psycho tests that enable a thorough assessment of work capacity and fitness for carriage of firearms, driving as well as the assessment of psychiatric disorders, which are the most delicate to assess.